2023
DOI: 10.3389/fpls.2023.1018626
|View full text |Cite
|
Sign up to set email alerts
|

Evaluationof compact air-induction flat fan nozzles for herbicide applications: Spray drift and biological efficacy

Abstract: Nozzles are the most critical component of a sprayer for pesticide applications. Recently, air-induction nozzles and twin flat-fan air-induction nozzles have started to be used for herbicide applications. In order to evaluate the potential of compact air-induction nozzles for herbicide spraying, this paper compares the effects of air-induction nozzles and standard flat-fan nozzles on spray atomization, deposition, drift, and weed control efficacy in maize and wheat. Droplet spectra were measured by a laser par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Wang et al [ 62 ] observed that there was no significant difference for the biological efficacy in weed control in wheat crops for different standard flat spray nozzles and air-induced flat spray nozzles. In all cases, the efficacy values were greater than 80%.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [ 62 ] observed that there was no significant difference for the biological efficacy in weed control in wheat crops for different standard flat spray nozzles and air-induced flat spray nozzles. In all cases, the efficacy values were greater than 80%.…”
Section: Resultsmentioning
confidence: 99%
“…Low-drift nozzle selection is very important in order to minimize spraying drift. Lately, several compact anti-drift air-induction nozzles have been studied and used since they can result in significant spray drift reduction while keeping high efficacy against weeds [35][36][37]. Ferreira et al [29] proved that the MUG11003 nozzle produced fewer driftable droplets and greater droplet size compared to other air induction nozzles.…”
Section: Crop Referencementioning
confidence: 99%
“…Alheidary [29], while studying different types of spray nozzles, found that the hollow cone spray nozzle resulted in the best deposition (0.06 µL cm −2 ) compared to other nozzle types (flat fan and air-induction flat fan) under the same operating conditions for ground application using a knapsack sprayer. Wang et al [30] found that air-induction nozzles performed better than standard flat fan nozzles, in general, for boom sprayer application in terms of increased deposition. The authors believe that the increased deposition was related to a greater potential for drift reduction.…”
Section: Treatmentsmentioning
confidence: 99%